Developing Mind Mapping-Based Pocketbook with Augmented Reality to Support Creative Thinking Skills in Pre-Service Mathematics Teachers - Duano Sapta Nusantara; Feri Tiona Pasaribu; Tria Gustiningsi; Abdul Halim Abdullah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2025)
Enhancing creative thinking skills (CTSs) is a critical competency for pre-service mathematics teachers, especially in responding to the demands of 21st-century learning. This study aims to develop a pocketbook based on mind mapping and supported by Augmented Reality (AR), integrated within a Project-Based Learning (PjBL) framework, to support creative thinking skills. The development process adopted the Plomp model, consisting of preliminary investigation, design, realization, testing, evaluation, revision, and implementation phases. The resulting instructional pocketbook focuses on secondary school mathematics content and includes a series of questions enhanced with AR features to support CTSs. The findings demonstrate that the developed mind mapping based pocketbook with AR effectively improves students' ability to think creatively and solve complex mathematical problems. This research contributes to the field of mathematics education by offering an innovative tool that combines visual mapping strategies, immersive technology, and active learning to better prepare future mathematics educators.